Interleukin 11 is upregulated in preeclampsia and leads to inflammation and preeclampsia features in mice. (February 2018) - Winship, Amy; Dimitriadis, Eva
Highlights: Decidual cell interleukin (IL) 11 blocks extravillous trophoblast invasion. IL11 levels in serum and placenta are upregulated in preeclampsia. Exogenous IL11 leads to increased systolic blood pressure and proteinuria in mice. Exogenous IL11 alters placental inflammatory cytokines and uNK cells in mice. Abstract: Preeclampsia is a dangerous pregnancy complication, which is often associated with fetal growth restriction and can have serious life-long effects for both mother and baby. While the establishment of the placenta in the first trimester is the sentinel event in the development of preeclampsia little is known of the critical mechanisms of placentation that lead to the syndrome. Locally produced inflammatory cytokines are thought to play a role in the development of preeclampsia. This review summarizes the evidence that interleukin 11 is dysregulated in preeclampsia and contributes to the initiation of preeclampsia via effects on placentation. It discusses the benefits and drawbacks of targeting IL11 as a novel treatment option for preeclampsia.